The use of complete dentures affects the nutritional status of the elderly: Penggunaan gigi tiruan lengkap mempengaruhi status gizi manula - Leny Sang Surya; Resa Ferdina; Intan Syafutri (Makassar Dental Journal PDGI Makassar, 2021)
Oral and dental health in the elderly needs special attention because it can affect general health. Complete denture is an alterna-tive treatment for tooth loss in the elderly because it can restore chewing function, appearance and social aspects and can im-prove nutritional status. The purpose of this study was to determine the effect of the use of CD on nutritional status in the el-derly. This quantitative research used analytical observation method with cross sectional study design. The study population was the elderly in the section of the Prosthodontics Baiturrahmah Dental Hospital and the samples were elderly who used CD and did not use CD selected by purposive sampling technique. Determination of nutritional status using the Body Mass Index (BMI), data were analyzed using the Chi-Square test. The results showed that the elderly who used CD had a normal nutritional status of 60%, while the elderly who did not use CD had a normal nutritional status of only 34.8% and the analysis Chi-Square showed a significance value of 0.000 (P<0.05). The conclusion of this study is that there is an effect of the use of CD on the nutri-tional status of the elderly at Baiturrahmah Dental Hospital, where using CD can improve nutritional status in the elderly.